Enhancing Curcumin’s therapeutic potential in cancer treatment through ultrasound mediated liposomal delivery - Radha, Remya (2024)
Improving the efficacy of chemotherapy remains a key challenge in cancer treatment, considering the low bioavailability, high cytotoxicity, and undesirable side effects of some clinical drugs. Targeted delivery and sustained release of therapeutic drugs to cancer cells can reduce the whole-body cytotoxicity of the agent and deliver a safe localized treatment to the patient. There is growing interest in herbal drugs, such as curcumin, which is highly noted as a promising anti-tumor drug, considering its wide range of bioactivities and therapeutic properties against various tumors. Conversely, the clinical efficacy of curcumin is limited because of poor oral bioavailability, low water solubility, instability in gastrointestinal fluids, and unsuitable pH stability. Drug-delivery colloid vehicles like liposomes and nanoparticles combined with microbubbles and ultrasound-mediated sustained release are currently being explored as effective delivery modes in such cases. This study aimed to synthesize and study the properties of curcumin liposomes (CLs) and optimize the high-frequency ultrasound release and uptake by a human breast cancer cell line (HCC 1954) through in vitro studies of culture viability and cytotoxicity. CLs were effectively prepared with particles sized at 81 ± 2 nm, demonstrating stability and controlled release of curcumin under ultrasound exposure. In vitro studies using HCC1954 cells, the combination of CLs, ultrasound, and Definity microbubbles significantly improved curcumin’s anti-tumor effects, particularly under specific conditions: 15 s of continuous ultrasound at 0.12 W/cm² power density with 0.6 × 10⁷ microbubbles/mL. Furthermore, the study delved into curcumin liposomes’ cytotoxic effects using an Annexin V/PI-based apoptosis assay. The treatment with CLs, particularly in conjunction with ultrasound and microbubbles, amplified cell apoptosis, mainly in the late apoptosis stage, which was attributed to heightened cellular uptake within cancer cells.